Behind bars: Evaluating the nutritional landscape — A review of dietary patterns provided in correctional facilities - K. Sanjeet; S. Mishra (Пищевые системы)
The quality of nutrition in correctional facilities plays a crucial role in the health of incarcerated individuals. This review investigates dietary patterns within these institutions, examining their nutritional adequacy and compliance with established guidelines. The review aims to assess the nutritional content of meals provided in correctional settings and their impact on inmate health. A systematic literature review was conducted, analyzing studies that evaluate meal composition, adherence to nutritional standards, and associated health outcomes for inmates. Data was synthesized from diverse correctional facilities to highlight common trends and disparities. Findings reveal pervasive nutritional deficiencies across correctional facilities. Many meals lack adequate fresh fruits, vegetables, and whole grains, relying heavily on processed foods high in sodium and sugar. Such imbalances can lead to significant health issues, including obesity, hypertension, and metabolic disorders among the incarcerated population. The review also highlights disparities based on facility types, geographic locations, and budgetary constraints, which influence the nutritional quality of meals. Addressing the nutritional deficiencies in correctional facilities is imperative for improving inmate health and facilitating rehabilitation. Implementing comprehensive meal planning, increasing access to fresh produce, and ensuring adherence to nutritional standards can enhance the dietary landscape in these settings. Future research should focus on effective interventions and policies aimed at improving nutritional offerings to support the health and well-being of incarcerated individuals.